2017
DOI: 10.1007/s11103-017-0584-x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and hormone analyses reveal mechanisms underlying petal elongation in Chrysanthemum morifolium ‘Jinba’

Abstract: Auxin regulates chrysanthemum petal elongation by promoting cell elongation. Transcriptomic analysis shows that auxin signal transduction may connect with other transcription factors by TCPs to regulate chrysanthemum petal elongation. As an ornamental species, Chrysanthemum morifolium has high ornamental and economic value. Petal size is the primary factor that influences the ornamental value of chrysanthemum, but the mechanism underlying the development of C. morifolium petals remains unclear. In our study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 51 publications
2
57
0
Order By: Relevance
“…Taking advantage of next‐generation sequencing, a number of differentially expressed genes were identified from a pairwise comparison of ray florets and disc florets of chrysanthemum (Liu et al ., ). Our previous study showed that auxin and some key transcription factors were involved in the growth of chrysanthemum petals (Wang et al ., ). In addition, CYCLOIDEA ( CYC )‐like genes have been reported as being involved in the regulation of flower symmetry in Asteraceae species (Broholm et al ., ; Huang et al ., ; Juntheikki‐Palovaara et al ., ; Kim et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Taking advantage of next‐generation sequencing, a number of differentially expressed genes were identified from a pairwise comparison of ray florets and disc florets of chrysanthemum (Liu et al ., ). Our previous study showed that auxin and some key transcription factors were involved in the growth of chrysanthemum petals (Wang et al ., ). In addition, CYCLOIDEA ( CYC )‐like genes have been reported as being involved in the regulation of flower symmetry in Asteraceae species (Broholm et al ., ; Huang et al ., ; Juntheikki‐Palovaara et al ., ; Kim et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…There are some reports on phytohormones that can affect the oral opening [19], and therefore, we explored the DEGs involved in eight phytohormone signal transduction pathways. The levels of endogenous AUX were much higher in the basal petals and application of exogenous indole-3-butyric acid (IBA) can enlarge the cell length in chrysanthemum [5]. Many unigenes involved in AUX signal transduction pathway were increasingly expressed with the ower opening of rose, suggesting that AUX signaling participated in petal development [37].…”
Section: Identi Cation Of Degs Involved In the Phytohormone Signal Trmentioning
confidence: 99%
“…79 TFs which were divided into eight gene family (Fig. 6, Table S10) were selected for further analysis because they may be involved in petal cell expansion [5,37]. In the MYB TF family, only ve out of twenty genes (Unigene36971, CL242.Contig2, CL10695.Contig2, Unigene11061, and Unigene30676) were up-expressed under relatively low temperature.…”
Section: Identi Cation Of Degs Of Transcription Factors (Tfs)mentioning
confidence: 99%
See 2 more Smart Citations